CCBC Choices: 1989 - Horning, Kathleen T.; Kruse, Ginny Moore; Lindgren, Merri V. (Cooperative Children's Book Center, 1990)
CCBC CHOICES is an annual list of recommended books for children and young adults selected by the librarians at the Cooperative Children’s Book Center, a library of the School of Education at the University of Wisconsin-Madison. CCBC CHOICES 1989 recommends 257 titles for children and young adults published in 1989. It includes a commentary on the 1989 publishing year, including statistics on the number of books by and about Africans and African Americans published for children and teens.
Keywords: Bibliographies; Children's Literature; Young Adult Literature